Analisis Interaksi Dan Respon Penonton Di Media Sosial Terhadap Sinetron “Asmara Gen Z” Dengan Menggunakan Teori Uses And Gratification - Qanitah Salma; Rini Sartika; Putri Handayani (Filosofi : Publikasi Ilmu Komunikasi, Desain, Seni Budaya, 2025)
This study aims to analyze the interaction and response of viewers on social media to the soap opera Asmara Gen Z using the Uses and Gratification theory. The research method used is a qualitative approach with interaction and response analysis, as well as in-depth interviews with active viewers. The results of the study indicate that the main motivation of viewers in watching the soap opera Asmara Gen Z is because of the presence of young actors and actresses who are relatable to their lives, an interesting and diverse storyline, and a hit soundtrack. This soap opera also succeeded in building hype through social media with active interaction from the players. These findings indicate that the soap opera Asmara Gen Z meets various audience needs, including cognitive, affective, personal identity, social integration and interaction, and escape needs. This study provides insight into how soap operas can create high engagement on social media and provides implications for entertainment content marketing strategies in the digital era.